Green financing and environmental protection / Siti Sarah Abdul Razak and Norli Ali - Abdul Razak, Siti Sarah; Ali, Norli (UiTM Press, 2023)
The climate crisis has exposed the financial sector to greater risks. One of the most important ways to combat climate change is by restoring the landscape of the planet, which is becoming one of the agendas in sustainable development goals (SDGs). In fulfilling this agenda, participation from organizations is essential and usually requires a significant amount of up-front investment capital and investment that usually has a long payback period. Therefore, dedicated investment funds like green financing have been used to finance such projects. This study investigated the effectiveness of green financing as a tool in financing project that supports the SDGs projects, particularly green investment projects such as environmental protection. Green financing plays an active role in the improvement of a company's profitability and supporting the sustainability that contributes to environmental protection. The results showed that there is a significant relationship between green financing and the performance of the firms that were listed in Bursa Malaysia which contributed to environmental protection activities. The findings of the study could provide insights for investors, and it may serve as a contributing factor to the development of the green financing market. In addition, these findings may assist environmentally aware investors holding positions in green finance for risk management decisions and developing portfolios.